2017
DOI: 10.1117/1.jbo.22.12.121709
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography in gynecology: a narrative review

Abstract: Abstract. Modern gynecologic practice requires noninvasive diagnostics techniques capable of detecting morphological and functional alterations in tissues of female reproductive organs. Optical coherence tomography (OCT) is a promising tool for providing imaging of biotissues with high resolution at depths up to 2 mm. Design of the customized probes provides wide opportunities for OCT use in gynecology. This paper contains a retrospective insight into the history of OCT employment in gynecology, an overview of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…In recent years, noninvasive imaging technologies, such as fluorescence, OCT, Doppler OCT, ultrasound, and photoacoustic imaging, have been developed to provide morphology and molecular contrast of biological tissue . Among them, OCT has the advantage over histologic tissue analysis (obtained by biopsy) in acquiring high resolution, microscopic images with a non‐invasive approach . Despite demonstrated success in various other medical fields, it has only undergone limited use in gynecology.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, noninvasive imaging technologies, such as fluorescence, OCT, Doppler OCT, ultrasound, and photoacoustic imaging, have been developed to provide morphology and molecular contrast of biological tissue . Among them, OCT has the advantage over histologic tissue analysis (obtained by biopsy) in acquiring high resolution, microscopic images with a non‐invasive approach . Despite demonstrated success in various other medical fields, it has only undergone limited use in gynecology.…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant global use of OCT in many fields of medicine [49][50][51][52][53], in urology, our study demonstrated the first use of this technique for examining the urethra [36]. This paper shows that the introduction of new technology-CP OCT-in conjunction with TVUS allows verification of tissue changes and assessment of the structures of the connective tissue matrix of the lower urinary tract at the level of their architectonics.…”
Section: Discussionmentioning
confidence: 80%
“…We proceeded from the results of our previous study [36], where the morphology of the female urethra was analyzed on cadaveric material and compared with CP OCT images. This fact and numerous studies on CP OCT visualization of mucous membranes in health and pathology [30,31,52,61,62] afford ground for confidence in the interpretation of CP OCT features, such as changes in the epithelium thickness and the state of connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant global use of OCT in many fields of medicine [29][30][31][32][33], in urology, ours was the first use of this technique for examining the urethra [22]. This paper shows that the introduction of 2.64 mm, respectively [27].…”
Section: Discussionmentioning
confidence: 81%